Borrowing Constraints and Portfolio Choice - Paxson, Christina (Quarterly Journal of Economics, 1990)
Journal Article Borrowing Constraints and Portfolio Choice Get access Christina Paxson Christina Paxson Princeton University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 105, Issue 2, May 1990, Pages 535–543, https://doi.org/10.2307/2937799 Published: 01 May 1990